Effects of Heat Waves and Light Deprivation on Giant Kelp Juveniles (Macrocystis pyrifera, Laminariales, Phaeophyceae) - Sánchez-Barredo, Mariana (Journal of phycology, 2020)
© 2020 Phycological Society of America.